2020
DOI: 10.3390/molecules25030714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Engineered Carbon Nanodiamonds on the Collapse Mechanism of Model Lung Surfactant Monolayers at the Air-Water Interface

Abstract: Understanding interactions between inhaled nanoparticles and lung surfactants (LS) present at the air-water interface in the lung, is critical to assessing the toxicity of these nanoparticles. Specifically, in this work, we assess the impact of engineered carbon nanoparticles (ECN) on the ability of healthy LS to undergo reversible collapse, which is essential for proper functioning of LS. Using a Langmuir trough, multiple compression-expansion cycles are performed to assess changes in the surface pressure vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several studies have reported on the altered surface properties and phase behavior of lipids using the Langmuir-Blodgett technique due to variations in temperature [15][16][17], different chain lengths of acyl lipids [18][19][20], compositions with other lipids [21][22][23], mixtures with other components [24][25][26] or particles [27][28][29], differences in subphases [30][31][32][33], oxidation and degradation [34][35][36], and pH changes [37][38][39]. Only a few research cases have thoroughly investigated hysteresis using the same technique, particularly for phospholipids, e.g., [6,29,[40][41][42][43][44]. Many articles discussing hysteresis studies are predominantly found in the context of mimicking meibomian lipid films [7,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the altered surface properties and phase behavior of lipids using the Langmuir-Blodgett technique due to variations in temperature [15][16][17], different chain lengths of acyl lipids [18][19][20], compositions with other lipids [21][22][23], mixtures with other components [24][25][26] or particles [27][28][29], differences in subphases [30][31][32][33], oxidation and degradation [34][35][36], and pH changes [37][38][39]. Only a few research cases have thoroughly investigated hysteresis using the same technique, particularly for phospholipids, e.g., [6,29,[40][41][42][43][44]. Many articles discussing hysteresis studies are predominantly found in the context of mimicking meibomian lipid films [7,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%